Respiratory-related activity patterns in preganglionic neurones projecting into the cat cervical sympathetic trunk. - Boczek-Funcke, Ansgar; Dembowsky, Klaus; Häbler, Heinz-Joachim; Jänig, Wilfrid; Michaelis, M. (The journal of physiology, 1992)
1. Activity in 233 single sympathetic preganglionic neurones that project to the superior cervical ganglion was analysed with respect to central components of respiration (phrenic nerve discharge) and to the afferent feedback generated by mechanical events occurring with ventilation in anaesthetized and artificially ventilated cats. 2. The activity in ninety-one neurones was modulated during the respiratory cycle in two ways: directly by the central inspiratory drive, and indirectly by ventilation-related blood pressure changes, acting via the systemic baroreceptors. The direct influence was prominent in vagotomized animals or those with a raised respiratory drive, and consisted of an inspiratory increase in activity and decreases of activity in early inspiration and postinspiration. The indirect influence (excitation due to baroreceptor unloading) usually dominated in normocapnic cats with intact vagus nerves. This population of neurones showed both similar reflex responses and a similar respiratory modulation of activity as postganglionic neurones supplying hindlimb skeletal muscle. 3. Sixty-one neurones discharged exclusively, or almost exclusively, during central inspiration. This discharge pattern neither depended on the integrity of vagal nor baroreceptor afferents. The activity of these neurones was abolished during hyperventilation and enhanced during hypercapnia. In the latter state, a small activation was often seen in stage II expiration. 4. In normocapnia the remainder of neurones (n = 81) exhibited no, or no pronounced, respiratory modulation of activity, except three neurones which showed a prominent expiratory pattern being of central and not of reflex origin. They were not a homogeneous population and included neurones exhibiting reflex responses similar to those of postganglionic neurones supplying hindlimb skin (n = 36), neurones responding to light (n = 4), and others (n = 41). 5. It is concluded that distinct types of thoracic preganglionic neurone differ with respect to respiratory modulation of their activity stemming from both central and reflex sources. Thus, the temporal profile of activity in these neurones in relation to respiration is another functional characteristic which can be used to distinguish between populations of sympathetic neurones.
Gesehen am 22.10.2024